Roseobacter clade bacteria are abundant in coastal sediments and encode a novel combination of sulfur oxidation genes - Lenk, Sabine; Moraru, Cristina; Hahnke, Sarah; Arnds, Julia; Richter, Michael; Kube, Michael; Reinhardt, Richard; Brinkhoff, Thorsten; Harder, Jens; Amann, Rudolf; Mußmann, Marc (The ISME Journal, 2012)
Roseobacter clade bacteria (RCB) are abundant in marine bacterioplankton worldwide and central to pelagic sulfur cycling. Very little is known about their abundance and function in marine sediments. We investigated the abundance, diversity and sulfur oxidation potential of RCB in surface sediments of two tidal flats. Here, RCB accounted for up to 9.6% of all cells and exceeded abundances commonly known for pelagic RCB by 1000-fold as revealed by fluorescence in situ hybridization (FISH). Phylogenetic analysis of 16S rRNA and sulfate thiohydrolase (SoxB) genes indicated diverse, possibly sulfur-oxidizing RCB related to sequences known from bacterioplankton and marine biofilms. To investigate the sulfur oxidation potential of RCB in sediments in more detail, we analyzed a metagenomic fragment from a RCB. This fragment encoded the reverse dissimilatory sulfite reductase (rDSR) pathway, which was not yet found in RCB, a novel type of sulfite dehydrogenase (SoeABC) and the Sox multi-enzyme complex including the SoxCD subunits. This was unexpected as soxCD and dsr genes were presumed to be mutually exclusive in sulfur-oxidizing prokaryotes. This unique gene arrangement would allow a metabolic flexibility beyond known sulfur-oxidizing pathways. We confirmed the presence of dsrA by geneFISH in closely related RCB from an enrichment culture. Our results show that RCB are an integral part of the microbial community in marine sediments, where they possibly oxidize inorganic and organic sulfur compounds in oxic and suboxic sediment layers.